2019
DOI: 10.1186/s42269-019-0061-6
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional impact of inclusion of garlic (Allium sativum) and/or onion (Allium cepa L.) powder in laying hens’ diets on their performance, egg quality, and some blood constituents

Abstract: Background: Many studies mentioned that using medicinal herbs and plants as feed additives to ruminants seems to be a recent trend depending on the availability and their cost but using them with monogastric animals and birds, as pharmaceutical tool, is available. As an example, the importance of garlic or onion in recent years, thanks to a wide range of useful properties, has been increasingly used as an additive in nutrition and protection of farm animals. Their action was manifested in a reduced expanding r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 32 publications
(40 reference statements)
2
15
0
Order By: Relevance
“…Mixing layer diets with 1–3% garlic powder could improve total immunoglobulin, but yolk height, egg weight, fertility, and hatchability were not affected in White Leghorns chickens ( Tesfaheywet et al, 2017 ; Meseret et al, 2018 ). A recent study conducted by Omer et al (2019) reported that the incorporation of garlic or onion powder or the mixture of them in laying hen diets could increase shell thickness and egg weight. In contrast, Reddy, Lightsey & Maurice (1991) and Chowdhury, Chowdhury & Smith (2002) did not find garlic paste or garlic oil affect egg weight.…”
Section: Nutritional Applications In Animalsmentioning
confidence: 99%
“…Mixing layer diets with 1–3% garlic powder could improve total immunoglobulin, but yolk height, egg weight, fertility, and hatchability were not affected in White Leghorns chickens ( Tesfaheywet et al, 2017 ; Meseret et al, 2018 ). A recent study conducted by Omer et al (2019) reported that the incorporation of garlic or onion powder or the mixture of them in laying hen diets could increase shell thickness and egg weight. In contrast, Reddy, Lightsey & Maurice (1991) and Chowdhury, Chowdhury & Smith (2002) did not find garlic paste or garlic oil affect egg weight.…”
Section: Nutritional Applications In Animalsmentioning
confidence: 99%
“…This finding suggests that diets with GLC, especially as much as 2 and 3% of the total rations, may preclude the chickens from infections, inflammation, or stress. These phenolic compounds in garlic powder could act as antimicrobial agents, and prevent the broiler chickens from infections and inflammation (Omer et al, 2019). Garlic contains allicin, alliin, ajoene, diallyl sulfide, dithiin, Sallylcysteine.…”
Section: Discussionmentioning
confidence: 99%
“…The fourth group infected with E. coli and supplemented with A. sativum improved serum MDA levels, which revealed a significant decrease in serum MDA levels compared with the infected non-treated group. This may occur due to the active components present in A. sativum, which have antioxidant activities that help eliminate free radicals and prevent cellular destruction (Omer et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The present study also showed an increase in serum NO levels in A. sativum supplemented chickens. The active compounds in A. sativum have antioxidant and immunostimulant effect, which NO generated during an immune response (Arreola et al 2015;Omer et al 2019). E. coli-infected chickens showed a significant increase in the serum NO.…”
Section: Discussionmentioning
confidence: 99%